Currency Integration and Bilateral Trade: Evidence from the Eurozone - Mealli, Fabrizia (Journal of Business and Economic Options, 2021)
The findings of this study provide valuable insights into the trade effects of adopting the euro within the European Economic and Monetary Union (EMU). By employing the gravity model of international trade, the study sheds light on how the common currency impacts bilateral trade and exports among EMU member countries. The estimated results reveal a significant positive effect of the euro on bilateral trade within the EMU. Specifically, the study finds that when both trading partners within the EMU use the euro as their currency, bilateral trade increases by approximately 12%. This suggests that the adoption of the euro facilitates trade integration among EMU member countries, leading to expanded economic exchange and collaboration. Moreover, the study highlights the positive impact of the euro on exports from EMU economies. The findings indicate that EMU countries experience an increase in exports of around 7% when trading with other EMU members using the common currency. This underscores the role of the euro in enhancing export competitiveness and facilitating market access for EMU exporters within the monetary union. The implications of these findings are particularly significant for countries considering joining the eurozone. The observed trade effects provide valuable policy insights for prospective eurozone members, suggesting that adopting the euro can potentially stimulate trade and enhance economic cooperation with existing EMU members. This underscores the importance of carefully assessing the economic implications and benefits of euro adoption for aspiring member countries. This study contributes to our understanding of the economic implications of currency unions, particularly within the context of the EMU. By highlighting the positive trade effects of the euro on EMU countries, the findings offer important policy implications for both existing and prospective eurozone members, emphasizing the role of currency integration in fostering economic growth and development within the European Union.